IMPLEMENTATION OF TEACHER RECRUITMENT AND SELECTION SYSTEM AT SD IT AL- WAHDAH TOJO UNA-UNA - Suci Indasari (Adisam Publisher, 2025)
In the field of education, educators and teachers play a crucial role in enhancing the quality of education. As a result, educational institutions require professionals who can effectively carry out their duties to achieve established goals. However, the situation of teachers in Indonesia still needs serious attention. One factor contributing to the low quality of education is that teachers do not always teach by their abilities. A key reason for this issue is the lack of a selective recruitment process, which fails to recognize the importance, role, and benefits of effective teacher recruitment. This study uses a qualitative, descriptive approach to explore various events, aspects, phenomena, and conditions within the research setting, drawing upon field knowledge. The findings indicate that the teacher recruitment system at SD IT Al-Wahdah Tojo Una-Una involves three main components: planning, strategy, and organization. The strategic stages of the recruitment process include conducting a teacher needs analysis, planning the requirements for teaching staff, disseminating information both internally and externally, screening applicants' documents, conducting oral interviews, calling selected candidates, and placing new teachers accordingly.